THE SPECTRAL PROPERTIES OF THE ONE-PARTICLE SCHODINGER OPERATOR ON THE TWO-DIMENSIONAL LATTICE - Yusupov, rabbim; Mavlanova , Mohinur (Журнал математики и информатики, 2021)
Some spectral properties of the Schrodinger operators, corresponding to energy operators-Hamiltonians of one and the system of two quantum particles moving on lattices, are studied by S.Albeverio, S.N.Lakaev, Z.Muminov, Faria da Veiga P.A.,Ioriatti L., and O’Carrol M/